Exploring the Characteristics of Psychological Development of Madrasah Aliyah Students from the Perspective of Islamic Education - Eka Putri Rahayu; Rayhan Alfauzan; Sandrina Muchtar (Gunung Djati Conference Series, 2026)
This study aims to describe the characteristics of psychological development among Madrasah Aliyah students, covering cognitive, emotional, and social aspects from the perspective of Islamic education. In addition, the study examines the factors influencing these developmental processes and analyzes the role of Islamic educational values in guiding the formation of students’ ways of thinking, emotional regulation, and social interaction skills in an integrated and continuous manner. The research employs a descriptive qualitative approach, with data collected through observations, in-depth interviews, and documentation. Primary data were obtained from students, teachers, homeroom advisors, and counselors, while secondary data were sourced from instructional documents and madrasah archives. Data analysis was carried out through the stages of reduction, presentation, and conclusion drawing using an interactive model to produce a comprehensive understanding of the psychological development phenomena. The findings indicate that students’ psychological development progresses in a complex manner and is influenced by learning stimulation, emotional dynamics, social relationships, and spiritual guidance. Students begin to develop abstract thinking skills but still require supervision. Emotionally, they face identity exploration, while socially they seek group acceptance. Islamic educational values play a significant role in guiding these developments, enabling the madrasah to shape students’ character in a holistic way.